Moving towards a mechanistic understanding of biostimulant impacts on soil properties and processes: a semi-systematic review - Roche, Dannielle; Rickson, Jane R.; Pawlett, Mark (Frontiers in Agronomy, 2024)
Biostimulants are gaining prominence in scientific research, with the potential to enhance plant productivity through benefits to crop yield/quality and tolerance to environmental stresses.Through possible improvements to nutrient use efficiency, they may also lessen the adverse environmental impacts of conventional inorganic fertilizer use in agriculture. The application of biostimulants is currently uncommon as a farming practice, with uncertain effectiveness in delivering these potential benefits. Current research focuses on biostimulant effects on plant physiological changes. There is little scientific evidence on the impact of biostimulants on soil properties (biological, physical or chemical) or soil functions. This knowledge gap should be addressed, considering the vital role of soil processes in the bioavailability of nutrients, as reflected in crop productivity. This review evaluates laboratory and field experimental work on the effectiveness of common, non-microbial biostimulants, with a focus on their modes of action within the soil matrix. Of 2,097 initial articles returned through the search strings, 10 were within the scope of this review. A common soil biostimulant mechanism emerges from this literature. This relates to the supply of nutrients provided by the biostimulants which stimulate native soil microbiology in mineralizing organic material in the soil, thus producing more bioavailable nutrients for plant uptake. Additionally, some articles link biostimulant effects to soil physical and chemical changes which in turn impact soil biology (and vice versa). However, there is inconsistent evidence to provide full support for these explanatory mechanisms. This review highlights the need for further research into the effect of biostimulants on the native soil microbiology and associated soil properties, to provide greater clarity on biostimulants' modes of action and greater mechanistic insights into how they can be used to improve crop production.